1972
DOI: 10.1177/00220345720510061001
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Dissolution: II. Action of Titanium Tetrafluoride

Abstract: Mechanisms by which titanium tetrafluoride (TiF4) reduces enamel solubility were investigated. An association was found between solubility reduction and the formation of a glaze on the enamel surface. Also, TiF4-treated enamel had higher levels of fluoride than enamel treated with acidulated phosphate-sodium fluoride. Solubility reductions and fluoride levels decreased slightly with washing but after 48 hours the fluoride level was still 60% of the maximum, and solubility reductions ranged between 64 and 70%.I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
1
9

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 6 publications
1
61
1
9
Order By: Relevance
“…The matrix, even though suggested to be removed prior to laboratorial analysis (17), may have been important to inhibit the progression of erosive lesions, especially when treated with TiF 4 . Some authors reported that TiF 4 produces a glaze on the dentin surface (6,18) and one of the strongest actual theories to explain this formation considers the direct interaction between titanium and the organic matrix (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The matrix, even though suggested to be removed prior to laboratorial analysis (17), may have been important to inhibit the progression of erosive lesions, especially when treated with TiF 4 . Some authors reported that TiF 4 produces a glaze on the dentin surface (6,18) and one of the strongest actual theories to explain this formation considers the direct interaction between titanium and the organic matrix (8).…”
Section: Discussionmentioning
confidence: 99%
“…Among the existing theories to explain its action, one is that titanium is capable of reacting with the oxygen atoms of the phosphate groups of the dental tissue, forming stable titanium oxides (7) or organometallic complexes that can act as a diffusion barrier (8).…”
Section: Introductionmentioning
confidence: 99%
“…6,8,12 The protective effect of TiF 4 is attributed to the acid-resistant surface coating formed by the fluoride-metal complex, which might lead to a mechanical protection of the surface. 14 Furthermore, the application of TiF 4 might lead to an increase in the enamel fluoride content.…”
Section: Discussionmentioning
confidence: 99%
“…This might enhance the depth of penetration of fluoride ions and promote the formation of CaF 2 . The titanium ions might play an important role as they might substitute calcium in the apatite lattice and show a strong tendency to complex with phosphate groups, forming stable titanium dioxide layer [14][15][16] . Moreover, it is suggested that titanium interacts with organic components of the enamel surface, leading to an increased fluoride uptake by enamel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation